Nonlinear Response for Neoplastic Transformation following Low Doses of Low Let Radiation - J. Leslie Redpath (SAGE Publishing, 2005)
There are now several independent studies that indicate that the dose-response for the endpoint of radiation-induced neoplastic transformation in vitro is non-linear for low linear energy transfer (LET) radiation. At low doses (<10 cGy) the transformation frequency drops below that seen spontaneously. Importantly, this observation has been made using fluoroscopic energy x-rays, a commonly used modality in diagnostic radiology, the practice of which is responsible for the majority of radiation exposure to the general public. Since the transformation frequency is reduced over a large dose range (0.1 to 10cGy) it is likely that multiple mechanisms are involved and that the relative contribution of these may vary with dose. These include the killing of a subpopulation of cells prone to spontaneous transformation at the lowest doses, and the induction of DNA repair at somewhat higher doses. Protective effects of low doses of low LET radiation on other cancer-relevant endpoints in vitro and in vivo have also been observed by several independent laboratories. These observations strongly suggest that the linear-nonthreshold dose-response model is unlikely to apply to the induction of cancer by low doses of low LET radiation in humans.